The Legionella pneumophila iraAB Locus Is Required for Iron Assimilation, Intracellular Infection, and Virulence - Viswanathan, V. K. (American Society for Microbiology, 2000)
Legionella pneumophila, a facultative intracellular parasite of human alveolar macrophages and protozoa, causes Legionnaires' disease. Using mini-Tn10 mutagenesis, we previously isolated a L. pneumophila mutant that was hypersensitive to iron chelators. This mutant, NU216, and its allelic equivalent, NU216R, were also defective for intracellular infection, particularly in iron-deficient host cells. To determine whether NU216R was attenuated for virulence, we assessed its ability to cause disease in guinea pigs following intratracheal inoculation. NU216R-infected animals yielded 1,000-fold fewer bacteria from their lungs and spleen compared to wild-type-130b-infected animals that had received a 50-fold-lower dose. Moreover, NU216R-infected animals subsequently cleared the bacteria from these sites. While infection with 130b resulted in high fever, weight loss, and ruffled fur, inoculation with NU216R did not elicit any signs of disease. DNA sequence analysis revealed that the transposon insertion in NU216R lies in the first open reading frame of a two-gene operon. This open reading frame (iraA) encodes a 272-amino-acid protein that shows sequence similarity to methyltransferases. The second open reading frame (iraB) encodes a 501-amino-acid protein that is highly similar to di- and tripeptide transporters from both prokaryotes and eukaryotes. Southern hybridization analyses determined that the iraAB locus was largely limited to strains of L. pneumophila, the most pathogenic of the Legionella species. A newly derived mutant containing a targeted disruption of iraB showed reduced ability to grow under iron-depleted extracellular conditions, but it did not have an infectivity defect in the macrophage-like U937 cells. These data suggest that iraA is critical for virulence of L. pneumophila while iraB is involved in a novel method of iron acquisition which may utilize iron-loaded peptides.